Associations Between Fetal Imprinted Genes and Maternal Blood Pressure in Pregnancy. Issue 6 (December 2016) - Petry, Clive J.; Sanz Marcos, Nuria; Pimentel, Gracielle; Hayes, M. Geoffrey; Nodzenski, Michael; Scholtens, Denise M.; Hughes, Ieuan A.; Acerini, Carlo L.; Ong, Ken K.; Lowe, William L.; Dunger, David B.
Abstract : In addition to maternal genes and environmental exposures, variation in fetal imprinted genes could also affect maternal blood pressure during pregnancy. Our objective was to test the associations between polymorphic variants in 16 imprinted genes and maternal mean arterial blood pressures in 1160 DNA trios from 2 established birth cohorts (the Cambridge Baby Growth and Wellbeing Studies) and seek replication in 1367 Hyperglycemia and Adverse Pregnancy Outcome Study participants. Significant univariate associations, all independent of fetal sex, were observed in the Cambridge cohorts, including FAM99A rs1489945 transmitted from the mother ( P =2×10 –4 ), DLK1 rs10139403 (mother; P =9×10 –4 ), DLK1 rs12147008 (mother; P =1×10 –3 ), H19 rs217222 (father; P =1×10 –3 ), SNRPN rs1453556 (father; P =1×10 –3 ), IGF2 rs6356 (father; P =1×10 –3 ), and NNAT rs6066671 (father; P =1×10 –3 ). In meta-analysis including additional independent Hyperglycemia and Adverse Pregnancy Outcome Study data, the association with maternally transmitted fetal DLK1 rs10139403 reached genome-wide significance ( P =6.3×10 –10 ). With the exception of fetal rs1489945 and rs217222, all of other associations were unidirectional and most were statistically significant. To further explore the significance of these relationships, we developed an allele score based on the univariate findings. The score was strongly associated with maternal blood pressure at 31 weeks ( P =4.1×10 –8 ; adjusted r 2 =5.6%) and 37 weeks of pregnancy ( P =1.1×10 –4 ; r 2 =3.6%), and during the last 2 weeks before parturition ( P =1.1×10 –10 ; r 2 =8.7%). It was also associated with gestational hypertension (odds ratio, 1.54 [range, 1.14–2.09] per allele; P =0.005; 45 cases and 549 controls). These data support the concept that fetal imprinted genes are related to the development of gestational hypertension. Abstract : Supplemental Digital Content is available in the text.